Ethnic interaction and integration in Gondär (Ethiopia): the case of the Amhara and Tigre, 1930–1970s - Tesfamichael Fentie Derso (Cogent Arts & Humanities)
This study focuses on the interaction and integration of the Amhara-Tigre people in Gondär from 1930 to the 1970s. Gondär is situated in the northwestern part of Ethiopia, in the Amhara Regional State. The aim was to fill the existing gap in knowledge. The study collected data from primary and secondary sources, including interviews with key informants and document reviews of books, journals, theses, and archives. The qualitative data was thoroughly examined, cross-checked, analyzed, and interpreted. The interaction and integration between the Tigre and Amhara in Gondär was peaceful and coexistent. Once the Tigreans permanently settled in the study area, they adopted the Amhara culture, values, language, and ways of life. Similarly, the Amhara people inherited new businesses such as masonry, carpentry, cart services, charcoal production, and others from their Tigrean counterparts. The historical interaction between the Amhara and Tigre ethnic groups resulted in the emergence of children with dual identities. These individuals, who are of both Amhara and Tigre descent, reside in the study area and are sometimes referred to as ‘double face jackets’.